Biblical hermeneutics : five views - Porter, Stanley E., 1956-; Stovell, Beth M., 1978-; Blomberg, Craig (Downers Grove, Ill. : IVP Academic, 2012)
Five experts in biblical hermeneutics gather here to state and defend their approach to the discipline. Contributors include: Craig Blomberg with the historical-critical/grammatical approach, Richard Gaffin with the redemptive-historical approach, Scott Spencer with the literary/postmodern approach, Robert Wall with the canonical approach and Merold Westphal with the philosophical/theological approach. --from publisher description.
Introduction : trajectories in biblical hermeneutics / Stanley E. Porter and Beth M. Stovell -- Five views of biblical hermeneutics. The historical-critical/grammatical view / Craig L. Blomberg. The literary/postmodern view / F. Scott Spencer. The philosophical/theological view / Merold Westphal. The redemptive-historical view / Richard B. Gaffin Jr. The canonical view / Robert W. Wall -- Responses. The historical-critical/grammatical response / Craig L. Blomberg. The literary/postmodern response / F. Scott Spencer. The philosophical/theological response / Merold Westphal. The redemptive-historical response / Richard B. Gaffin Jr. The canonical response / Robert W. Wall -- Interpreting together : synthesizing five views of biblical hermeneutics / Stanley E. Porter and Beth M. Stovell.
Includes bibliographical references and indexes.
Keywords: Bible -- Hermeneutics; Bible -- Hermeneutics